up there - Nguyen, Christina (Stimulus: A Medical Humanities Journal, 2023)
"up there" highlights the first time I saw death in the emergency room. I remember how my mind almost burst in the frenzy of the moment. As I eventually calmed down and left my shift, I reflected often on the memory: how am I supposed to feel? What would have it felt like to be the one laying in the bed?